New Insights into Prostate Cancer Diagnosis and Treatment (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This book addresses the latest studies and research findings on the detection, diagnosis and treatment of prostate cancer. It is intended to provide an overview of topics such as risk factors including genetic and environmental predispositions, as well as diagnosis and the latest available therapies and their complications in the field of prostate cancer. The goal is to enable better and more comprehensive care and to improve the quality of life of patients with prostate cancer.